Infeksi Parasit Trematoda Pada Saluran Gastrointestinal Sapi Potong Di Peternakan Rakyat Kecamatan Candipuro Kabupaten Lampung Selatan - Ramadhan, H S; Maradon, G G; Candra, A A; Pertiwi, V R; Habsari, I K; Usman, N A; Putri, D D (Politeknik Negeri Lampung, 2024)
Candipuro District is an agricultural and plantation area, apart from that the people also raise beef cattle. Beef cattle are used as a source of meat and as a source of fertilizer for agriculture in the area. There are still some farmers in Candipuro District who raise beef cattle using the traditional method, where the cattle are still kept behind the farmer's house and are given forage in the form of grass. Providing forage in the form of grass can have an impact on livestock health, especially on exposure to gastrointestinal parasites. Gastrointestinal parasite infections are a common problem in cases of gastroenteritis in livestock throughout the world. This can have quite a broad impact, especially on the health of the veterinary community and the health of the livestock itself throughout the world, especially in developing countries. This research was carried out using sample testing using the sedimentation method and also McMaster. Data obtained from the results of testing 193 fecal samples in 14 villages in Candipuro District using the floating and EPG methods, the results obtained are as in table 1. The incidence rate of Trematode parasite infection in Candipuro District is 46.56%. Of the 14 villages, there was a 0% incidence rate of trematode worm cases in Banyumas Village. And then the highest prevalence was in Karya Mulya Sari village at 13.97%. The conclusion of this research is the incidence of Trematode parasite infection in Candipuro District. Of the 193 samples examined, 76 samples were positively infected with Trematode parasites with the species Fasciola sp. and Paramphistomum sp.